Analisis Kemudahan Penggunaan dan Kegunaan pada Sikap Penggunaan Mikro Kredensial Universitas Ciputra - Putri, Natashya Geiska; Budidharmanto, Lexi Pranata; Tjahjono, Laura Mahendratta; Subadi, Lucky Cahyana; Yahya, Ellen Lawrencia (Universitas Multi Data Palembang, 2024)
Micro-credentials are considered a potential solution for enhancing the quality of human resources in Indonesia, especially among university students. This study investigates factors influencing the acceptance and use of micro-credentials using the Technology Acceptance Model (TAM). It focuses on the roles of Perceived Usefulness (X1) and Perceived Ease of Use (X2) in shaping Attitude Toward Use (Y) of micro-credentials. A quantitative approach was employed, collecting data through questionnaires from 24 students at Ciputra University Surabaya. The data were analyzed using SPSS with multiple linear regression analysis. The results indicate that Perceived Usefulness (X1) significantly impacts Attitude Toward Use (Y), while Perceived Ease of Use (X2) does not have a significant individual effect. These findings offer insights into how universities can utilize micro-credentials to improve student engagement and learning experiences, preparing them for the workforce. This study supports the development of education and the enhancement of human resource quality in Indonesia, demonstrating the relevance and effectiveness of micro-credentials in higher education.